BS ISO 13914. Soil, treated biowaste and sludge. Determination of dioxins and furans and dioxin-like polychlorinated biphenyls by gas chromatography with high resolution mass selective detection (HR GC-MS). (7th October 2021) - British Standards Institution
No abstract available